2001
DOI: 10.1051/rnd:2001127
|View full text |Cite
|
Sign up to set email alerts
|

Sheep embryos derived from FSH/eCG treatment have a lower in vitro viability after vitrification than those derived from FSH treatment

Abstract: -In the non breeding period, the effect of two superovulatory treatments (eCG/FSH in single dose or FSH alone in four decreasing doses) on the production of embryo quality following in vitro viability after vitrification procedures was investigated using forty-four adult Sarda breed ewes. In sheep treated with eCG/FSH, the mean number of corpora lutea was significantly (P < 0.05) higher (11.8 ± 4.0 vs. 8.05 ± 3.8), although the recovery rate was significantly (P < 0.01) lower (74.6 vs. 59.9) than with FSH alon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
15
2
2

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 39 publications
5
15
2
2
Order By: Relevance
“…In ewe lambs, Kelly et al (2005) reported that oocytes following a pFSH-based superovulatory treatment that included eCG that were matured and fertilised in vitro, had higher blastocyst rates than did the oocytes recovered after a treatment without eCG (Kelly et al 2005). Embryos produced in vivo following a simplified pFSH'eCG superovulatory treatment can have fewer cells and, therefore, lower viability and tolerance to cryopreservation than do embryos derived from treatments based on repeated doses of pFSH (Leoni et al 2001;Forcada et al 2011). In our study, the numbers of total and DCHFDA-positive cells in blastocysts from in vitro-produced oocytes did not differ significantly between the two superovulatory treatment groups which suggests that the negative effect of the simplified protocol on embryo quality is not apparent in the follicular wave that follows the oestrus induced by the superovulatory treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In ewe lambs, Kelly et al (2005) reported that oocytes following a pFSH-based superovulatory treatment that included eCG that were matured and fertilised in vitro, had higher blastocyst rates than did the oocytes recovered after a treatment without eCG (Kelly et al 2005). Embryos produced in vivo following a simplified pFSH'eCG superovulatory treatment can have fewer cells and, therefore, lower viability and tolerance to cryopreservation than do embryos derived from treatments based on repeated doses of pFSH (Leoni et al 2001;Forcada et al 2011). In our study, the numbers of total and DCHFDA-positive cells in blastocysts from in vitro-produced oocytes did not differ significantly between the two superovulatory treatment groups which suggests that the negative effect of the simplified protocol on embryo quality is not apparent in the follicular wave that follows the oestrus induced by the superovulatory treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Induced ovulation is a routine laboratory procedure in mice, pioneered by Runner & Gates (1954), and has been successfully applied to other small laboratory species such as rats (Goh et al 1992, Jiang et al 1999 and rabbits (Treloar et al 1997), as well as larger domestic eutherians such as cow (Donaldson & Ward 1986, Lopes da Costa et al 2001, horse (Niswender et al 2003), sheep (Leoni et al 2001), pig (Amirov et al 1998), and goat (Kiessling et al 1986). In mice, induced ovulation is used not only for the production of large numbers of oocytes, but also for the establishment of timed pregnancies that proceed to term with the birth of young (Edwards & Gates 1959, Edwards & Fowler 1960, Beaumont & Smith 1975, Spindle & Goldstein 1975.…”
Section: Discussionmentioning
confidence: 99%
“…As reported, the dosage of gonadotropin to induce superovulation should be based on body weight (Rahman et al, 2014). Superovulation can be induced by 5-10 IU eCG in female mice (Kanter et al, 2004;Wei et al, 2014), 500-600 IU eCG in ewes (Leoni et al, 2001;Simonetti et al, 2008;Forcada et al, 2011), and 2000-3000 IU eCG in cows (Bó and Mapletoft, 2014). During the biphasic follicular growth in guinea pigs, the first phase culminates on cycle Days 10-11 (Bland, 1980;Hutz et al, 1990), and the dominant follicle is transformed on cycle Day 12 (Shi et al, 2000).…”
Section: Introductionmentioning
confidence: 99%